Moderately Concentrated Acetonitrile‐containing Electrolytes with High Ionic Conductivity for Durability‐oriented Lithium‐Ion Batteries. Issue 16 (17th August 2021) - Matsuoka, Naoki; Kamine, Hirokazu; Natsume, Yutaka; Yoshino, Akira
Abstract: Electrode protection additives for acetonitrile (AN)‐containing electrolytes play an important role for the usability of such electrolytes since it is decomposed reductively and electrochemically on the negative electrode of lithium‐ion batteries. The durability of electrolytes containing AN with low concentration of lithium salt was investigated by electrochemical measurements to achieve the desired battery performance derived from high ionic conductivity. The reductive decomposition of AN was suppressed by adding vinylene carbonate and ethylene sulfite as solid electrolyte interface formation additives. The high temperature durability performance with various positive electrode chemistries was improved by applying pyridine as a stabilizer for LiPF6 . The AN‐containing electrolyte enhances low temperature performance and long‐term performance at high temperatures due to higher molecular mobility and a low electrode interface barrier. This electrolyte not only increases the capacity by enabling the usage of thicker electrodes, but also reduces the total cost of battery production. Abstract : Electrode protection additives for acetonitrile‐containing electrolytes are investigated to achieve extremely high ionic conductivity without using superconcentrated formulations. Reductive decomposition of acetonitrile is suppressed by combining vinylene carbonate and ethylene sulfite as solid electrolyte interface formation additives. High temperature durability performance with various positive electrodes is improved by applying pyridine as a stabilizer for LiPF6 .